Inauthentic self-presentation on facebook as a function of vulnerable narcissism and lower self-esteem. (January 2020) - Grieve, Rachel; March, Evita; Watkinson, Jarrah
Abstract: This study was the first to delineate the role of grandiose narcissism and vulnerable narcissism, in addition to self-esteem and self-monitoring, in predicting authentic self-presentation on Facebook. Facebook users ( N = 155) answered questions about their personality as well as the persona they present on Facebook, and Euclidean distances quantified the congruence between the two personas. Self-monitoring (ability to modify self-presentation) was included as a control variable in regression analysis. As hypothesised, grandiose narcissism predicted more congruent presentation between the true self and the Facebook self, while vulnerable narcissism predicted a greater difference between the two personas. In contrast to predictions, self-esteem was not associated with congruence between the two selves; however, a follow-up moderation analysis revealed a significant self-esteem—vulnerable narcissism interaction. Specifically, for individuals with average and low levels of self-esteem, there is more incongruence between the true self and the Facebook self as a function of increased vulnerable narcissism. Given the psychological benefits associated with authentic self-presentation on Facebook, these findings inform understanding of the negative affective processes of vulnerable narcissists and their self-presentation on this popular social networking medium. Highlights: Examined congruence between the true self and the Facebook self. Grandiose narcissism predicted greater congruence. Vulnerable narcissism predicted less congruence. Effects of vulnerable narcissism are increased at low-medium levels of self esteem. Facebook allows narcissistic subtypes to differentially meet self presentation needs.